THE ROLE OF ELECTRONIC WORD OF MOUTH (E-WOM) IN MODERATING THE INFLUENCE OF PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS (A STUDY ON CONSUMERS OF LUXCRIME BLUR & COVER TWO WAY CAKE PRODUCTS IN DENPASAR CITY) - Ni Luh Ayu Yuliantari; Putu Yudi Setiawan, I Gusti Ayu Ketut Giantari, I Nyoman Nurcaya (Adisam Publisher, 2025)
Consumer purchase decisions for cosmetic products are influenced by various factors, including product quality and the impact of electronic word of mouth (e-WOM). In today's digital era, e-WOM has become one of the key elements shaping consumer perceptions of a product, especially in the highly competitive beauty industry. This study aims to examine and explain the role of e-WOM in moderating the influence of product quality on consumer purchase decisions. The research was conducted on consumers of Luxcrime Blur & Cover Two Way Cake in Denpasar City, with a sample size of 150 consumers obtained using a non-probability sampling method. Data collection was carried out by distributing questionnaires. The analytical technique employed was Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results of the analysis indicate that: Product quality has a positive and significant effect on consumer purchase decisions, e-WOM has a positive but not significant effect on consumer purchase decisions, and e-WOM moderates by strengthening the influence of product quality on consumer purchase decisions.